2014
DOI: 10.1007/s00264-014-2282-5
|View full text |Cite
|
Sign up to set email alerts
|

Dorsal percutaneous screw fixation of delayed or nonunion of scaphoid fractures

Abstract: Purpose The purpose of the present study is to evaluate scaphoid delayed fractures or nonunions treated by percutaneous fixation with MRI correlations. Methods We evaluated 33 consecutive scaphoid delayed unions or nonunions treated by dorsal percutaneous fixation at a mean 16 months (range, seven to 48 months) after the operation. There were 31 male and two female patients with an average age of 29 years (range, 25-33 years). Results Pre-operative MRI revealed no signs of avascular necrosis. At the latest fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Ultimately, 23 studies were included for final data extraction and analysis. 11,12,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ►Fig. 1 outlines the results of the literature search and article selection.…”
Section: Resultsmentioning
confidence: 99%
“…Ultimately, 23 studies were included for final data extraction and analysis. 11,12,15,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] ►Fig. 1 outlines the results of the literature search and article selection.…”
Section: Resultsmentioning
confidence: 99%
“…Vanhees et al 15 have reported achieving 94% union in a case series of 16 patients treated using a percutaneous technique where the mean time to union was 4 months (17 weeks). Recently, favorable results and high union rates with percutaneous techniques have been reported in multiple studies, [12][13][14] although the exact time to union has not been reported in all the studies. The major risk factors involved in the failure of treatment for this condition are the duration between the injury and the surgical treatment, as well as the localization of the nonunion in the proximal pole 25 (►Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The union rate and healing potential with percutaneous [11][12][13][14][15] and arthroscopically assisted [16][17][18][19][20] techniques for the treatment of scaphoid nonunion have not been discussed at length. Indeed, comparative studies of different treatment options are rare in the literature.…”
mentioning
confidence: 99%
“…Interosseal vascularization of the proximal bone pole (70-80%) originates from the radial artery branch which enters the bone along the dorsal ridge at the level of the waist. Given such anatomy, after a fracture there is a risk of vascular insufficiency and consequential development of avascular necrosis [5], particularly of the upper bone pole [1]. Delay in diagnosis leads to a variety of adverse outcomes such as delayed union, nonunion, decreased grip strength, smaller range of motion, and osteoarthritis of the radiocarpal joint [6].…”
Section: Introductionmentioning
confidence: 99%